THE INCIDENCE AND MORPHOLOGICAL FEATURES OF THROMBOCYTOPENIA IN PREGNANCY - Dilafruz L. Zaynutdinova; Shaira A. Babadjanova (Central Asian Journal of Medicine, 2022)
The research has focused onthe frequency, causes and consequences of thrombocytopenia acquired at all stages of pregnancy. The purpose of which was identification of the frequency and characteristics of thrombocytopenia at different stages of pregnancy. Clinical material for the study was obtained from 30 pregnant women aged 18-35 years who were treated from January 2021 to March 2022 in the department of pathology of pregnant women of the Tashkent Medical Clinic of the Ministry of Health of the Republic of Uzbekistan.